Fetishism and Fluidity: Jeanette Winterson"s Narratives of Diverse Pleasure and Desire - Shareena Z. Hamzah (2018)
Jeanette Winterson is an influential and award-winning contemporary British writer whose books combine aspects of philosophy, spirituality, and sexual politics. This thesis explores Winterson’s treatment of the body, gender, and sexuality to examine the fluidity of desire and pleasure, focusing mainly on Oranges Are Not The Only Fruit, Boating For Beginners, The Passion, Sexing The Cherry, Written on The Body, The PowerBook, and The Daylight Gate. The thesis illustrates the ‘alternative’ fetishism that Winterson consistently presents through the deconstruction of the body and the remapping of gender and sexuality. The study suggests that in Winterson’s work there is queering of fetishism that opens up a new perspective on the psychoanalytical reading of such texts. A queer reading of fetishism is an extremely useful analytical tool and the thesis suggests that insufficient critical attention has been paid to the possibilities it presents. The thesis uses an amalgamation of established and contemporary theoretical approaches to the body, gender, and sexuality to understand the challenge to boundaries that occurs in Winterson’s writing. Psychoanalytical theories from Freud, Lacan, Foucault, and Butler are employed, combined with an interdisciplinary span of contemporary literary criticism from post-structuralist, feminist, and cultural materialist perspectives. The study argues that Winterson refashions discourses of sexuality, identity, and gender through alternative fetishism to demonstrate the existence of diverse and fluid desire in the self and the other. The scope of fetishism in this thesis is not only limited to sex; there are chapters on bodily fetishism, food fetishism, and sexual fetishism. The thesis argues that through images of queer bodies, Winterson’s writing challenges the meaning of gender, sexuality, and identity and opens a new portal in the reading of diverse pleasure and desire as she commingles orthodox, normative, and contemporary notions of ‘fetishistic’ desire to create an alternative view of the subject.